If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 2 = 8x + -1(3x + -1) Reorder the terms: 2 + -1x = 8x + -1(3x + -1) Reorder the terms: 2 + -1x = 8x + -1(-1 + 3x) 2 + -1x = 8x + (-1 * -1 + 3x * -1) 2 + -1x = 8x + (1 + -3x) Reorder the terms: 2 + -1x = 1 + 8x + -3x Combine like terms: 8x + -3x = 5x 2 + -1x = 1 + 5x Solving 2 + -1x = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + -1x + -5x = 1 + 5x + -5x Combine like terms: -1x + -5x = -6x 2 + -6x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + -6x = 1 + 0 2 + -6x = 1 Add '-2' to each side of the equation. 2 + -2 + -6x = 1 + -2 Combine like terms: 2 + -2 = 0 0 + -6x = 1 + -2 -6x = 1 + -2 Combine like terms: 1 + -2 = -1 -6x = -1 Divide each side by '-6'. x = 0.1666666667 Simplifying x = 0.1666666667
| -8x-40=7c-12+13x | | 0.19x=1.52 | | X/6-9=-8 | | 3X+5Y=550 | | 12X+2Y=517 | | -6x+4=5x+14-13x | | 4x-8/3=4 | | 4x+3=10-3x | | 12-(1/3)= | | 6x+35=-x | | 8x+9=12x-5 | | 6v+14=8v+24 | | 12-1/3= | | -2x+1-(-3x+3)=-4+(x-2) | | 12r=18(r+.5) | | -5x+2=10-8x | | r=6(r+.5) | | .3333x+5=.16666(2x-5) | | 12x-3y-10= | | Inx-in(x+3)=6 | | Y/3-y=4 | | 6(2x+4)=8x-3 | | r=6(2r+1) | | -2(3x-1)-4x=5x-(3x-6) | | -12n-(4n+5)=16-3n | | -10-bracket(-7)+2= | | 1/6×5= | | 3/2=3x-4/7 | | -8-(8)= | | 1/6×5 | | y-4x+110=0 | | x^2-9x+y^2=0 |